Effect of Effectiveness of Application Used Cooperative Learning Model Type Numbered Head Together (NHT), Teams Games Tournament (TGT) and Course Review Horay (CRH) against Increased Critical Thinking Skill of Students: (Experimental Study in Class fifth grade Social Science Subject In Cluster three Sub District Garawangi, Kuningan Regency) - Fitriyani, Yani; Supriatna, Nana (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This research was conducted because of the low critical thinking of students on social studies, this study aims to determine the Effectiveness of the application Cooperative Learning Model Type Numbered Head Together (NHT), Teams Games Tournament (TGT) and Course Review Horay (CRH) on Increasing Critical Thinking skill of Students in Social Studies. This type of research was quasi-experimental research, with a Counterbalance design research design. The subject in this study were fifth grade students of Gugus III Garawangi sub-district, Kuningan regerency, class V SDN Pakembangan Garawangi sub-district, class V SDN kutakembaran 1 Garawangi sub-district, and Class V SDN Kutakembaran 2 Garawangi sub-district, all schools are located in Kuningan District, West Java, where each class was an experimental class. Data collection techniques used are instrument test in this study was the multiple choice questions. Data analysis used to the analisis of statistic. The results of data analysis used statistic tests with t-test (independent samples t-test) at the 95% level of confidence obtained value tcount> ttable and probability value sig. (2-tailed) < 0.05, this shows that there are differences in the students' critical thinking skills so that the hypothesis is accepted, the results show the results of the mean of student that the Cooperative Learning Model Numbered Head Together (NHT), Teams Games Tournament (TGT) and Course Review Horay (CRH) are effectively used to improve students' critical thinking skills in social studies subject in class fifth of Cluster 3 sub-District of Garawangi, Kuningan Regency, west java